Knowledge Management Practices: Issues and Challenges (With s pedal reference to Chhattisgarh Academic Institutions) - Isaac, Mr.; Sahu , Nidhi; Dansena, Jyoti (Gyan Management Journal, 2010)
view considers knowledge to be present in ideas, judgments, talents, root causes,perspectives and concepts. Knowledge provides the ability to respond to novel situations.Management is the full utilization of information and data, coupled with the potential of kills and competencies. Knowledge management is about enhancing organizational-: :tiveness. Efforts to measure intellectual capital and to assess the effectiveness of knowledge applications should help us understand the extent to which we are managing knowledge This paper is concerned with an experimental approach about the Knowledge Management performed in the higher educational institutions in Chhattisgarh with respect to the support needs etc. The survey also found that most organisations did not have an explicit management strategy, or if they did, the majority of employees were not aware of it. A percentage of respondents believed that their Chairman/Director/Principal/CE::uragedknowledgesharing.